cAMP-dependent phosphorylation of bovine lens alpha-crystallin. - Spector, A (1985)
This communication reports that the A1 and B1 chains of bovine lens alpha-crystallin are phosphorylated. The conclusion is based on the following evidence: (i) When soluble preparations from lens cortex are incubated with [gamma-32P]ATP, a cAMP-dependent labeling of a high molecular weight protein is obtained. (ii) After NaDodSO4/PAGE, the label is found in two bands with Mr 22,000 and 20,000, corresponding to the B and A chains of alpha-crystallin, respectively. (iii) Isoelectric focusing indicates that the radioactivity is almost exclusively in bands with pI values of 5.58 and 6.70, corresponding to the A1 and B1 chains, respectively. (iv) Similar results are obtained in experiments of [32P]orthophosphate incorporation in lens organ culture. (v) Analyses of the digested protein indicate the label is exclusively in phosphoserine. (vi) 31P NMR analyses of native, proteolytically digested, and urea-treated alpha-crystallin gives a chemical shift of 4.6 ppm relative to 85% H3PO4 at pH 7.4, suggesting that the phosphate is covalently bound to a serine in the protein. An abundance of approximately one phosphate per four or five monomer units was found. (vii) Similar results were obtained by chemical analyses of independently prepared alpha-crystallin samples. The results are consistent with the view that the A1 and B1 chains arise as result of the phosphorylation of directly synthesized A2 and B2 polypeptides. It is suggested that this metabolically controlled phosphorylation may be associated with the terminal differentiation of the lens epithelial cell and the intracellular organization of the lens fiber cell.